Phthalates esters disrupt demersal fish behavior: Unveiling the brain-gut axis impact - Liuqingqing Liu; Xinyao Li; Xianxiang Luo; Xiao Wang; Linjia Liu; Zixi Yuan; Cuizhu Sun; Hao Zheng; Elvis Genbo Xu; Fengmin Li (Ecotoxicology and Environmental Safety)
The widespread use of plasticizers like phthalate esters (PAEs) has led to environmental and health concerns. The neurobehavioral toxicity of these compounds in marine environments, particularly regulated by the “brain-gut” axis, remains unclear, especially concerning wild demersal fish of high ecological value. Our investigation into the behavioral effects of three common PAEs, i.e., dimethyl phthalate (DMP), di-n-butyl phthalate (DBP), and di(2-ethylhexyl) phthalate (DEHP), and their molecular mechanisms on juvenile Sebastes schlegelii, revealed alarming results from molecular to population levels. After a 20-day foodborne exposure at a low marine environmental concentration (1.0 μg g−1), we observed that all three PAEs significantly increased the thigmotaxis (behavioral tendency to stay close to physical boundaries) and mobility of juvenile fish by 28.2–59.4 % and 23.3–74.5 %, respectively, indicating anxiety-like behavior of fish. DEHP exhibited the most pronounced effects, followed by DBP and DMP. PAEs accumulated in the juvenile fish in the order of brain > liver > gut > muscle, with DEHP showing the highest brain concentrations (23.2 ± 2.98 μg g−1). This accumulation led to oxidative damage, inflammatory responses, and neurodegenerative changes in the optic tectum, resulting in cholinergic system dysfunction. In the gut, PAEs caused inflammatory lesions, disrupted the gut barrier, and altered the gut microbiome, exacerbating the neurotoxicity via “brain-gut” communication. These findings underscore the significant neurobehavioral toxicity of PAEs, emphasizing their critical impact on fish behavior. We also stress the crucial need for further research on fish and other marine species beyond the laboratory scale to fully understand the broader implications of PAE exposure in marine ecosystems and to guide future conservation efforts.